A cross-sectoral analysis of climate change risk drivers based on companies' responses to the CDP's climate change information request - Markus Groth; Annette Brunsmeier (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
Companies are increasingly concerned with current and future climate change risks that have the potential to generate a substantial change in their business operations, revenue and/or expenditure. Therefore, the paper focusses on the companies' perspective and aims to create a higher awareness of companies' risk drivers when it comes to specific challenges of different sectors as well as each company within its sector. Based on companies' responses to the CDP's climate change information request 2013, including 125 companies from Germany, Austria and Switzerland, the paper presents a detailed companies' perspective on climate-related risk-drivers, comprising i) changes in regulation, ii) changes in physical climate parameters and iii) changes in other climate-related developments. Hence, the paper provides insights into climate change and adaptation related risks for companies. Furthermore, the results also facilitate a comparison of risk drivers between and within sectors. This also enables companies to i) position themselves regarding the potential threat they might be facing now and in the future, ii) assess their competitive advantages and disadvantages as well as prioritize risk drivers they have to deal with by evaluating their own position within the sector-specific analysis. Regarding specific threats companies are facing, they furthermore have the possibility to take good practices and innovative ideas from companies out of different sectors into consideration, aiming for an efficient and effective adaptation to climate change. Thus, the study's findings can also serve as an innovative starting point for further research as well as the practical implementation of adaptation measures.
Keywords: C83; D22; D81; L20; M20; M48; Q54; 330; business sectors; CDP climate change information request; climate change adaptation; climate change mitigation; climate reporting; risk drivers